Digital Transformation of Finance in Educational Institutions: A Systematic Literature Review on Fintech Implementation - Rahmad Dani Wahe; Muryani Arsal (Journal AGENCY, 2026)
This study aims to systematically examine the implementation of financial technology (fintech) and cashless payment systems (cashless society) in the context of Islamic boarding schools (pesantren) as an effort to minimize the risks associated with conventional transactions. The method used is a Systematic Literature Review (SLR) with a PRISMA approach. Data were obtained from the Google Scholar database using the keywords (“financial technology” OR fintech) AND (“digital payment” OR “cashless society”) AND (“Islamic boarding school” OR pesantren). The inclusion criteria comprised empirical research articles published in the last five years and not in the form of SLR articles. The selection process resulted in seven articles that were analyzed using a thematic approach. The findings indicate that the implementation of fintech-based payment systems in pesantren can reduce the risk of physical money loss, improve the accuracy of real-time transaction recording, strengthen parental monitoring mechanisms over students’ financial usage, and enhance transaction efficiency within the pesantren environment. Furthermore, digital systems strengthen transparency and accountability in pesantren financial management through the availability of documented transaction trails. However, successful implementation is highly influenced by the readiness of technological infrastructure, users’ level of digital literacy, and internal policy support from the pesantren. This study provides a conceptual foundation for developing safer, more transparent, and sustainable digital financial systems in pesantren.